Zastosowanie agentów programowych w handlu elektronicznym - Jelonek, Dorota (Application of software agents in electronic commerce, 2006)
Despite the rapid emergence of Internet-based electronic transactions, many users are still unfamiliar with the system and find it difficult to buy and sell products in the cyber marketplace. The agent-based virtual marketplace system, where agents take care of the transactions for individual users, has been suggested to solve this problem. Intelligent software agents are autonomous computational software entities that are especially meant to provide pro-active resource discovery and resolve information impedance of information consumers and providers. A software agent exhibits a number of features that make it different from other traditional components: autonomous, goal-oriented, collaborative, flexible, self-starting, communicative, adaptive and mobile.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 323-330